The Observance of Impoliteness Found in the Utterances Produced by the Characters of Paranorman Movie - Khristiandie Hartanto; Katharina Rustipa; Yulistiyanti Yulistiyanti (Universitas Dian Nuswantoro, 2022)
Abstract. This study aimed at finding out the impoliteness strategy produced by the characters in Paranorman movie. Employing a pragmatic analytical framework, this study is qualitative. The data were utterances produced by the characters in Paranorman movie, whereas the contexts were dialogues. The research used Paranorman movie script and movie as sources. The researcher was the primary instrument, with the datasheet as a secondary. The researcher collected data by analyzing documents by note-taking. The data were analyzed using a reference (pragmatic inference). The research findings reveal the following. First, the characters in Paranorman use four kinds of impoliteness strategies. They are bald on record, positive, negative, and sarcastic. Second, each impoliteness strategy has its own representation. Direct, clear, and unambiguous statements are used to express impoliteness. Positive impoliteness occurs as disassociating from others, calling the other names, and using taboo words. Negative impoliteness occurs as condescending, scorning, or ridiculing the other. Sarcasm or mock politeness is only performed by using insincere politeness. This is the most representation. Third, the movie shows three responses, namely no response, accepting, and countering the face attack. Countering a face attack has two parts, namely offensive and defensive.Keywords: impoliteness strategy, negative impoliteness, positive impolitenessAbstrak. Penelitian ini bertujuan menemukan strategi ketidaksopanan yang diucapkan oleh para tokoh di film Paranorman. Penelitian ini adalah penelitian kualitatif dengan orientasi pragmatic analytical framework. Data penelitian berupa ujaran yang diucapkan oleh para tokoh pada film Paranorman, sementara konteksnya adalah dialog. Sumber data adalah film Paranorman dan skripnya. Peneliti bertindak sebagai instrument utama, sedangkan lembar pencatat sebagai instrumen sekunder. Peneliti mengumpulkan data melalui analisis dokumen dengan cara note-taking. Data dianalisis menggunakan pragmatic inference. Berikut adalah temuan penelitian. Pertama, tokoh pada film Paranorman menggunakan empat macam strategi ketidaksopanan. Strategi tersebut adalah bald on record, positive, negative, dan sarcasm. Kedua, setiap strategi memiliki representasinya sendiri. Pernyataan langsung, jelas, dan tidak ambigu dipakai untuk mengekspresikan ketidaksopanan. Positive impoliteness terjadi saat menjauhkan hubungan dengan yang lain, dengan cara calling the other names, dan using of taboo words. Negative impoliteness terjadi saat merendahkan orang lain dengan scorning atau ridiculing orang lain. Sarcasm atau mock politeness dilakukan hanya dengan menggunakan insincere politeness. Ketiga, data menunjukan adanya tiga respons terhadap ketidaksopanan, yaitu no response, accepting, dan countering the face attack. Countering a face attack ada dua macam, yaitu offensive dan defensive.Kata kunci: strategi ketidaksopanan, ketidaksopanan negatif, ketidaksopanan positif